Israel's wars, 1947-93 - Bregman, Ahron (Warfare and history., 2000)
The book provides a fascinating overview of Israel's wars with the Palestinians and the Arabs. It is an exciting and informative history which analyses the effects of fifty years of constant conflict on the lives of the Israeli people.